Arterial Blood Gases and Cardiorespiratory Parameters in Etorphine-Medetomidine-Midazolam Immobilized Free-Ranging and Game-Farmed Southern White Rhinoceroses (Ceratotherium simum simum) Undergoing Electro-Ejaculation - Meuffels, Janine; Bertschinger, Henk; Tindall, Brendan; Pohlin, Friederike; Luther-Binoir, Ilse; Trivedi, Shweta; Boshoff, Christiaan R.; Lueders, Imke (Frontiers in Veterinary Science, 2022)
With the rapid loss of individuals in the wild, semen cryopreservation has gained importance to safeguard the genetic diversity of white rhinoceroses (Ceratotherium simum). For semen collection via electro-ejaculation, immobilization of free-ranging individuals requires the potent opioid etorphine, which is routinely combined with azaperone, but causes hypoxemia, hypercarbia, acidemia, muscle rigidity, tachycardia and systemic hypertension. In this study, the suitability of two alternative immobilization protocols including etorphine, medetomidine and midazolam at different doses (high vs low etorphine) was evaluated in adult white rhinoceros bulls in two different management systems (free-ranging vs game-farmed) and undergoing electro-ejaculation. Fourteen free-ranging (Group 1) and 28 game-farmed rhinoceroses (Group 2) were immobilized with ≈2.5 µg/kg etorphine (high dose), ≈2.5µg/kg medetomidine, ≈25 µg/kg midazolam and 1500-1700 IU hyaluronidase and received ≈2.5µg/kg of butorphanol intravenously at first handling. Twenty game-farmed animals (Group 3) received ≈1 µg/kg etorphine (low dose), ≈5 µg/kg medetomidine, ≈25 µg/kg midazolam and 1700 IU hyaluronidase. Respiratory rate, heart rate and peripheral hemoglobin oxygen saturation (SpO2) were measured at 5-minute intervals; non-invasive oscillometric blood pressures and arterial blood gases at first handling and before reversal of the immobilization; serum clinical chemistry analytes and hematocrit at first handling. Generalized mixed models (fixed factors: group, time, recumbency; random factor: individual rhinoceros) were applied to compare longitudinal changes between free-ranging and game-farmed rhinoceroses immobilized with the higher etorphine dose (Groups 1 and 2), and between the two protocols tested in the game-farmed rhinoceroses (Groups 2 and 3). All animals were successfully immobilized, presented with normal lactate concentrations (< 5 mmol/L), experienced no muscle tremors and recovered uneventfully. Hypoxemia and hypertension persisted throughout the immobilization in all groups. Acidemia and hypercarbia were absent in Group 1, but present in the game-farmed animals. The lower etorphine dose in Group 3 resulted in significantly longer induction times, however, tachycardia was not observed. SpO2 was higher for sternal versus lateral recumbency. Semen rich fractions were recovered following electro-stimulation in 46 out of the 62 animals. Our findings suggest that etorphine-medetomidine-midazolam provides effective immobilization with fewer side effects compared to previous reports in white rhinoceroses and is suitable for successful electro-ejaculation.